Strategy of PT Pelindo Terminal Petikemas Surabaya Region's Social and Environmental Responsibility (TJSL): Environmental and Educational Programs In Building Corporate Image - Chelsy Intania Marsyanda Putri; Diana Amalia (International Journal of Social, Economic, and Business, 2026)
This study examines how PT Pelindo Terminal Petikemas implements its Environmental and Social Responsibility (TJSL) strategy to build and strengthen corporate image. The research is grounded in the four-step Public Relations model (Cutlip, Center, & Broom) and the Triple Bottom Line framework, positioning TJSL not merely as philanthropy but as a strategic instrument for legitimacy, stakeholder trust, and sustainable reputation.  Using a descriptive qualitative approach, data were collected in 2025 through in-depth interviews and document analysis, involving four informants from internal units and external beneficiaries.  The findings show that Pelindo Terminal Petikemas applies a dual-track program formulation—combining corporate initiatives with responsiveness to community requests—supported by structured planning tools such as Theory of Change/Logical Framework and impact measurement (e.g., SROI).  TJSL communication is executed through multi-platform strategies and coordination with corporate communication, contributing to measurable image outcomes such as stakeholder recognition, awards, public satisfaction, and media exposure (PR Value).  Key challenges include limited resources for social mapping across geographically dispersed terminals, which affects program precision and requires adaptive stakeholder engagement..